2018
DOI: 10.2147/cmar.s171912
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum LAMC2 is associated with lymph node metastasis and predicts poor prognosis in penile squamous cell carcinoma

Abstract: PurposeMolecular biomarkers, especially serologic factors, have been widely applied in cancer diagnosis and patient follow-up. However, there are few valuable prognostic factors in penile squamous cell carcinoma (PSCC). Here, the authors investigated whether laminin gamma 2 (LAMC2) expression, especially serum LAMC2 (sLAMC2) level, was a suitable prognostic factor that could aid in the prediction of survival in PSCC.Patients and methodsThis study included 114 PSCC patients. Reverse transcription-quantitative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…immunohistochemistry Immunohistochemistry (IHC) staining for HHLA2, PD-L1, CD8, and CD4 was accomplished by a professional pathologist. [23][24][25] After deparaffinization, rehydration, antigen retrieval, endogenous peroxidase inactivation, and blocking non-specific binding, the 4 µM-thick sections were incubated with primary antibodies (anti-HHLA2: Sigma-Aldrich, HPA055478; anti-PD-L1: cell signaling technology, CST #13684; anti-CD8: CST, #85336; anti-CD4: Abcam, ab252199) at 4°C overnight. Then, the slides were incubated with a corresponding secondary antibody and visualized by using a DAKO EnVision Detection System (Dako).…”
Section: Methodsmentioning
confidence: 99%
“…immunohistochemistry Immunohistochemistry (IHC) staining for HHLA2, PD-L1, CD8, and CD4 was accomplished by a professional pathologist. [23][24][25] After deparaffinization, rehydration, antigen retrieval, endogenous peroxidase inactivation, and blocking non-specific binding, the 4 µM-thick sections were incubated with primary antibodies (anti-HHLA2: Sigma-Aldrich, HPA055478; anti-PD-L1: cell signaling technology, CST #13684; anti-CD8: CST, #85336; anti-CD4: Abcam, ab252199) at 4°C overnight. Then, the slides were incubated with a corresponding secondary antibody and visualized by using a DAKO EnVision Detection System (Dako).…”
Section: Methodsmentioning
confidence: 99%
“…The PSCC cell lines (Penl1, Penl2, and 149Rca), which were previously established by our group [21‐23], and the lung squamous carcinoma cell line H596 (ATCC HTB‐178, American Type Culture Collection, Manassas, VA, USA) were cultured in Dulbecco's modified Eagle's medium (Gibco, Grand Island, NY, USA) supplemented with 10% heat‐inactivated fetal bovine serum (Gibco, Grand Island, NY, USA) at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The luciferase reporter assay confirmed that miR-548c-3p interacted with LAMC2 3’UTR, which is also known as the laminin γ2 chain gene. Recent results suggest that LAMC2 could function as an oncogene to enhance the progression of many types of cancer, including penile squamous cell carcinoma [ 23 ], esophageal squamous cell carcinoma [ 24 ], gastric cancer [ 25 ], tongue squamous cell carcinoma [ 26 ], and colorectal cancer [ 27 ]. Silencing of LAMC2 reversed the EMT, invasion, and metastasis abilities [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%